1989
DOI: 10.1136/pgmj.65.768.725
|View full text |Cite
|
Sign up to set email alerts
|

Chronic active hepatitis: a sixteen year survey at a district general hospital

Abstract: Summary: Over a period of 16 years There were 7 deaths, three unrelated to liver disease. Survival analysis gives an 86% 5-year survival and 56% 10-year survival. Twenty four patients were treated with steroids (and 6 additionally with azathioprine); 15 (63%) were steroid responsive and 9 were non-responsive. In five patients steroids were successfully discontinued but in 10 patients severe symptomatic relapse occurred on steroid reduction below 7.5-10 mg/day. Steroid non-responders were not typical CAH, 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
2
14
2
Order By: Relevance
“…We found that the prevalence of autoimmune hepatitis in Singapore was four per 100 000, with no difference in prevalence between the three major races in Singapore. This is lower than the figures reported by Norway, 7 UK 8 and Iceland 9 . It may also be an underestimation because 20% of the patients in our catchment area are seen at other hospitals.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We found that the prevalence of autoimmune hepatitis in Singapore was four per 100 000, with no difference in prevalence between the three major races in Singapore. This is lower than the figures reported by Norway, 7 UK 8 and Iceland 9 . It may also be an underestimation because 20% of the patients in our catchment area are seen at other hospitals.…”
Section: Discussioncontrasting
confidence: 62%
“…The incidence and prevalence of AIH in Norway from 1986 to 1995 was reported as 1.9 × 10 5 and 16.9 × 10 5 , respectively, which was twice that reported for the same country in 1981 7 . This is also higher than previous reports from UK 8 and Iceland, 9 which could be explained by the prospective nature of the study and the better recognition of AIH.…”
Section: Introductioncontrasting
confidence: 67%
“…They found that the incidence and prevalence of AIH were similar to that of PBC (incidence 1.6/100 000 and prevalence 14.6/100 000) and almost double that of PSC (incidence 1.31/100 000 and prevalence 8.5/100 000). The rates of AIH found in this study were about twice those found in studies of idiopathic CAH in Iceland 30 and AIH as a cause of CAH in Sweden 31 and England 32 …”
Section: Disease Incidence and Prevalencesupporting
confidence: 46%
“…The rates of AIH found in this study were about twice those found in studies of idiopathic CAH in Iceland 30 and AIH as a cause of CAH in Sweden 31 and England. 32 Type II autoimmune hepatitis, associated with liverkidney-microsomal (LKM) antibodies, is much less common than type I AIH; however, no formal studies of incidence or prevalence rates have been performed. It was first formally described in 1987 and appears to be much more common in southern Europe than in either northern Europe or the USA.…”
Section: Disease Incidence and Prevalencementioning
confidence: 99%
“…We identified 17 studies describing the population incidence of AIH ( table 1 ) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Some of the manuscripts failed to clarify whether the study was population-based.…”
Section: Aihmentioning
confidence: 99%